2019
DOI: 10.3892/ol.2019.10383
|View full text |Cite
|
Sign up to set email alerts
|

Pleural fluid due to papillary thyroid cancer

Abstract: We report herein a rare case of massive pleural effusion caused by papillary thyroid cancer, which was accompanied by multiple pulmonary metastasis. A 91-year-old male patient presented with shortness of breath due to massive right pleural fluid. Cytological specimens, which were obtained from pleural fluid by thoracentesis, and was consistent with that observed in surgically resected thyroid cancer 6-year previously. Immunocytochemical staining of the cells was positive for cytokeratin (CK)-7, CK-19, and posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(101 reference statements)
1
2
0
2
Order By: Relevance
“…When examining our data closely, 70% of all cases that developed a pleural effusion died within 15 years, and the survival after development of pleural effusion was from 0.1 to 82.8 months with a median survival of 15 months. This is similar to prior studies that found pleural effusion preceded death by a median of 10-11 months (17,18). Specifically, most patients were dying from respiratory failure or a complication of fluid accumulation (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When examining our data closely, 70% of all cases that developed a pleural effusion died within 15 years, and the survival after development of pleural effusion was from 0.1 to 82.8 months with a median survival of 15 months. This is similar to prior studies that found pleural effusion preceded death by a median of 10-11 months (17,18). Specifically, most patients were dying from respiratory failure or a complication of fluid accumulation (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Malignant pleural effusion has previously been demonstrated to be associated with poor outcomes in other types of malignancy (12,13,14,15,16). It is noted that malignant pleural effusion complicates the clinical course in 0.6% of adult patients with papillary thyroid cancer and greatly shortens survival time in all cases (17,18,19,20,21,22,23,24,25,26). Our data support these studies, and we further demonstrated that the hazard ratio was highest for patients with lung metastases who developed a pleural effusion, when compared to other prognostic variables.…”
Section: Discussionmentioning
confidence: 99%
“…El derrame pleural debido al cáncer de tiroides diferenciado es una etiología poco común, muy rara como presentación inicial al momento del diagnóstico 5 .…”
Section: Discussionunclassified
“…Las metástasis a distancia son infrecuentes, sin embargo, constituyen una de las principales causas de mortalidad 4 . El derrame pleural asociado a cáncer de tiroides es una etiología muy poco frecuente, según la ultima revisión de literatura, se han notificado 51 casos en el mundo 5 .…”
Section: Introductionunclassified
“…Differentiated thyroid cancer (DTC), including papillary thyroid cancer, follicular thyroid cancer, and oncolytic thyroid cancer, accounts for >90% of all thyroid cancers [ 2 , 3 ]. Lung represents the most commonly involved organ by metastases from DTC, followed by bone [ 4 ], whereas metastasis to pleural is much less common, occupying nearly 0.6% [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%